Are railways 'climate friendly'? - Givoni, M; Brand, C; Watkiss, P (Alexandrine Press, 2009)
Rail is usually considered a green mode of passenger transport, at least greener than the car and plane in terms of its relative impact on climate change. It is therefore only natural that rail will play an increasing role in meeting demand for transport when the aim is to reduce environmental pollution associated with transport operation. Yet, referring to rail as green has many limitations and can be misleading. In this context, the paper aims to examine the environmental impact from rail transport and to show how the above generalization depends on many different factors. Attention is focused on comparing different trains (e.g. diesel vs. electric, and in the latter examining how environmental impacts depend on the sources used to generate the electricity) and different modes (train vs. car and plane). The paper also examines the scope for improving the environmental performance of rail through technical and operational measures. The paper concludes by identifying how and where rail can play a role in achieving a more sustainable transport system.